Polarized fluorescence of a crystal having uniaxially oriented molecules by a carbazole-diyl-bridged macrocage. Issue 26 (14th June 2019) - Hashimoto, Hikaru; Inagaki, Yusuke; Momma, Hiroyuki; Kwon, Eunsang; Yamaguchi, Kentaro; Setaka, Wataru
Abstract : An axially oriented π-electron system is achieved in a single crystal of a macrocage molecule, and polarized fluorescence of the single crystal was observed. Abstract : Polarized fluorescence derived from a molecular structure is characteristic of π-electron systems. Uniaxial molecular alignment can be realized by a crystal of macrocage molecules with a bridged π-electron system. Here, the polarized fluorescence of a single crystal of a carbazole-diyl-bridged macrocage due to the unidirectional orientation of the carbazole moiety inside was observed.